2018
DOI: 10.1103/physrevb.98.014508
|View full text |Cite
|
Sign up to set email alerts
|

Theory of tunneling spectroscopy of normal metal/ferromagnet/spin-triplet superconductor junctions

Abstract: We study the tunneling conductance of a ballistic normal metal / ferromagnet / spin-triplet superconductor junction using the extended Blonder-Tinkham-Klapwijk formalism as a model for a c-axis oriented Au / SrRuO3 / Sr2RuO4 junction. We compare chiral p-wave (CPW) and helical p-wave (HPW) pair potentials, combined with ferromagnet magnetization directions parallel and perpendicular to the interface. For fixed θM , where θM is a direction of magnetization in the ferromagnet measured from the c-axis, the tunnel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…To understand the nature of the induced minigap, we calculate the differential conductance of a Normalmetal(N)/Insulator(I)/F/TSC junction based on a recent theoretical model [37]. This model was developed particularly for Au/SRO113/SRO214 junctions, but can be applied to our system by considering that the barrier heights Z 1 and Z 2 correspond to the Au/STO/SRO113 and SRO113/SRO214 interfaces, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the nature of the induced minigap, we calculate the differential conductance of a Normalmetal(N)/Insulator(I)/F/TSC junction based on a recent theoretical model [37]. This model was developed particularly for Au/SRO113/SRO214 junctions, but can be applied to our system by considering that the barrier heights Z 1 and Z 2 correspond to the Au/STO/SRO113 and SRO113/SRO214 interfaces, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, the most promising candidate had been the chiral p-wave (i.e., p x + ip ywave) pairing 4 , which is spin-triplet with broken timereversal symmetry (TRS). The spin-triplet pairing was widely accepted since it is consistent with a variety of experiments such as polarized-neutron-scatterings 5 , halfquantum vortices 6,7 , the transport measurements [8][9][10][11][12][13][14][15] , and in particular the nuclear-magnetic-resonance (NMR) measurement 16 . There were also a number of theoretical studies supporting the spin-triplet scenario [17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 83%
“…3(a) and 3(b) and cylindrical in Fig. 3(c), where the effective mass 15 is respectively set to ( mx , my , mz ) = (1.0, 1.0, 1.0) and (1.3, 1.3, 16.0) with mν = m ν /m N . The barrier potential is z 0 = 0 in Fig.…”
Section: Tunnelling Spectroscopy Along C Axismentioning
confidence: 99%
“…Recent experimental works predict that the formation of Andreev Bound State (ABS) [95] and the flow of supercurrents [96] in SVs can be tuned and control via orientation of magnetization. Furthermore, it was also reported that at the ballistic junction of N|F|Triplet SC in Sr 2 RuO 4 [80], the orientation of magnetization can even control the pairing potential.…”
Section: Introductionmentioning
confidence: 97%
“…To understand feasibility of ferromangetism and superconductivity, and also the role of magnetization in F|S hybrids, many superconducting spintronic SVs had been extensively studied theoretically [76][77][78][79][80][81][82][83][84][85][86] and experimentally [87][88][89][90][91][92][93][94][95][96]. Previous works on F|S heterostructure and superconducting SVs strongly indicates that the superconducting critical temperature is dependent on the orientation of magnetization.…”
Section: Introductionmentioning
confidence: 99%